Analisis Biaya Relevan dalam Membuat Keputusan Menolak atau Menerima Pesanan Khusus pada UMKM MILOL.FOOD Jember - Khanifatul Khusna; Indicha Nasya Dwi Putri (Universitas Teknologi Surabaya, 2023)
Abstract. The aims of this research to find out relevant cost information that influencesmanagement's decision to reject or accept orders. The tools used in this method isrelevant costs. From the results of the research that has been carried out, milal.food'scriteria for special orders have been fulfilled, namely the existence of idle capacity andthe separation between normal sales and special order sales. So the decision taken bymilal.food to decide to accept special orders is correct because the costs incurred toproduce special orders are lower than the selling price of the order. Keywords: MSMEs, Relevant Price, Special Orders.